Exploring the Moderating Roles of Family-Work Conflict in the Relationship Between Work-Family Conflict and Teacher Well-Being - Uslukaya, Alper; Demirtas, Zulfu; Alanoglu, Muslim; Zincirli, Muhammed (Wiley, 2025)
Teachers well-being has a significant influence on their quality of life, as well as on students' emotions, behaviors, and cognitions. Although there is evidence of a negative relationship between teachers' experience of work-family conflict (WFC) and family-work conflict (FWC) with their well-being, we have no information on how the interaction of these two experiences relates to teacher well-being. Therefore, this study aims to examine the relationships between the interaction of WFC and FWC and teacher burnout and job engagement. The participants included 529 teachers from the Elaz & imath;& gbreve; provincial center in T & uuml;rkiye. According to the results of the structural equation modeling using Bayesian estimation, the positive relationship between WFC and burnout, as well as the negative relationship with work engagement, is stronger under high FWC conditions but significantly weakens under low FWC conditions. Therefore, we conclude that WFC and FWC interact to affect teacher well-being more negatively. The current study concludes with several theoretical and practical implications.
Keywords: burnout; family-work conflict; work engagement; work-family conflict